2017
DOI: 10.1038/nsmb.3355
|View full text |Cite
|
Sign up to set email alerts
|

Cotranslational folding of spectrin domains via partially structured states

Abstract: How do the key features of protein folding, elucidated from studies on native, isolated proteins, manifest in cotranslational folding on the ribosome? Using a well-characterized family of homologous α-helical proteins with a range of biophysical properties, we show that spectrin domains can fold vectorially on the ribosome and may do so via a pathway different from that of the isolated domain. We use cryo-EM to reveal a folded or partially folded structure, formed in the vestibule of the ribosome. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
167
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(176 citation statements)
references
References 51 publications
(63 reference statements)
8
167
1
Order By: Relevance
“…A range of structural and biophysical studies have indicated that certain NCs can form secondarystructure and even simple tertiary-structure motifs within the ribosome exit tunnel: the dimensions of the exit tunnel permit the formation of -helices within the central and lower tunnel regions, the formation of a small zinc-finger motif at the lower tunnel region and the formation of a -hairpin motif of transmembrane helices at the vestibule (Woolhead et al, 2004;Lu & Deutsch, 2005;Kosolapov et al, 2009;Bhushan et al, 2010;Nilsson et al, 2015). While the 20 Å width of the ribosome exit tunnel vestibule seems to preclude the formation of higher-order tertiary structure, simple tertiary-structure formation for smaller proteins has been found to be possible, such as a partially folded three-helix bundle at the exit of the vestibule (Nilsson et al, 2017).…”
Section: The Ribosome Exit Tunnel: a Site For Elongation Regulation Amentioning
confidence: 99%
See 2 more Smart Citations
“…A range of structural and biophysical studies have indicated that certain NCs can form secondarystructure and even simple tertiary-structure motifs within the ribosome exit tunnel: the dimensions of the exit tunnel permit the formation of -helices within the central and lower tunnel regions, the formation of a small zinc-finger motif at the lower tunnel region and the formation of a -hairpin motif of transmembrane helices at the vestibule (Woolhead et al, 2004;Lu & Deutsch, 2005;Kosolapov et al, 2009;Bhushan et al, 2010;Nilsson et al, 2015). While the 20 Å width of the ribosome exit tunnel vestibule seems to preclude the formation of higher-order tertiary structure, simple tertiary-structure formation for smaller proteins has been found to be possible, such as a partially folded three-helix bundle at the exit of the vestibule (Nilsson et al, 2017).…”
Section: The Ribosome Exit Tunnel: a Site For Elongation Regulation Amentioning
confidence: 99%
“…D73, 509-521 'senses' the passage of NCs. It orchestrates co-translational events including translational arrest at the elongation step of protein biosynthesis (Nakatogawa & Ito, 2001;Murakami et al, 2004) and limited folding of the NCs Nilsson et al, 2017), and represents a major hub for the recruitment of molecular chaperones, NC-modifying enzymes and the translocation machinery Balchin et al, 2016).…”
Section: The Ribosome Exit Tunnel: a Site For Elongation Regulation Amentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the entire cotranslational folding pathway must be considered when interpreting the effect of a pause in translation. We anticipate that an optimal translation protocol [48] could be predicted with knowledge of the substructure-specific folding and translation rates, as well as their propensities for forming non-native interactions, including interactions with the surface of the ribosome [49]. In addition, an optimal translation protocol is likely to be affected by the presence of misfolded intermediates, which may be avoided by increasing the local translation rate [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Even if it's not my own line of research, it's been quite an experience to help bring this new technology to Sweden. And, of course, we couldn't resist the temptation to integrate cryo-EM in some of our own projects: we now use APs to immobilize newly folded protein domains in the ribosome exit tunnel, and solve the structures using cryo-EM (35,36) (Fig. 8).…”
Section: Reflections: Membrane Protein Serendipitymentioning
confidence: 99%